Development of bottled ready-to-rink flavored mature coconut water using D-Optimal mixture design - Aba, Richard Paolo M.
In the Philippines, young coconut (9 months) water is a popular beverage consumed for its sensory properties and nutrient content. Contrary to this, mature coconut (11-12 months) water is discarded due to its poor sensory properties. The main objective of the study was to develop a bottled ready-to-drink (RTD) flavored mature coconut water using D-optimal mixture design. To achieve this, the study was divided into three (3) objectives – (1) documentation of collection and distribution practices of mature coconuts through key informant interview followed by screening of different varieties of mature coconut water for RTD flavored beverage, (2) optimization of the combination of mature coconut water, calamansi, and stevia, and (3) validation and characterization of the optimum RTD flavored mature coconut water developed. Key informant interview revealed that documented collection of mature nuts included choosing coconuts directly under a developing bud (tapatan) and at a stage where brown streaks appear on the nuts (batik). Coconuts were harvested using a sharp knife attached to a long bamboo pole (pagkakawit) followed by onsite husking (pagtatabas) prior transportation to a copra farm. Further, all varieties (Laguna Tall – LAGT, Catigan Green Dwarf – CATD, and Tacunan Green Dwarf – TACD) may be used for beverage development. Varietal screening revealed that LAGT was advantageous due to its availability and high water content. Consequently, LAGT was chosen for beverage development, with pH, sweetness, sourness, and overall acceptability selected for desirability-based numerical optimization. The models predicted that the formulations containing 88.60-91.19 g/100 mature coconut water, 8.00-10.41 g/100g calamansi, 0.53-0.94 g/100g stevia, and 0.20 g/100g turmeric were the optimum range with desirability score ranging from 0.703 to 0.808. Validation studies using the optimized combination exhibited desirable physicochemical, proximate, vitamin, mineral, and phytochemical profiles, with increase in sodium, calcium, and zinc. Sensory evaluation indicated a score of ‘6 – like slightly’, suggesting the potential of the formulation to address poor sensory characteristics of mature coconut water. Overall, this research provided valuable insights for valorization of coconut water varieties instead of discarding them as waste, and a possible solution to utilize this ‘waste’ through beverage development.